Penerapan SA 500 pada Prosedur Audit Utang Usaha - Dila Arigra Putri; Habibie, Samas Adimisa Mishbah (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
Accounts Payable Audit is an essential part of the financial statement examination process to ensure the accuracy and completeness of a company's liabilities. Auditing Standard (SA) 500 on Audit Evidence serves as the primary guideline for auditors in collecting and evaluating sufficient and appropriate audit evidence. This study discusses the application of SA 500 in the audit procedures of accounts payable, starting from planning, implementation, to the documentation of audit evidence. The method used is literature study and procedural analysis based on SA 500. By understanding SA 500, auditors can conduct audits more effectively and ensure that accounts payable are recorded accurately in accordance with applicable standards.